2018
DOI: 10.1038/s41598-018-22082-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Liver Steatosis and Affected Pathways with Molecular Imaging and Proteomic Profiling

Abstract: Current assessment of non-alcoholic fatty liver disease (NAFLD) with histology is time-consuming, insensitive to early-stage detection, qualitative, and lacks information on etiology. This study explored alternative methods for fast and quantitative assessment of NAFLD with hyperspectral stimulated Raman scattering (SRS) microscopy and nanofluidic proteomics. Hyperspectral SRS microscopy quantitatively measured liver composition of protein, DNA, and lipid without labeling and sensitively detected early-stage s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…In this study, we showed that multiplexed immunoassays in nanocapillaries permitted simultaneous analysis of nine signaling pathways in cultured SH-SY5Y cells. Notably, nanofluidic protein PTM profiling is ideally suited for applications on clinical specimens due to its ultrasensitivity, where nanograms of tissue lysates are sufficient for the detection of picograms of proteins of interest [12,13,21,52]. Furthermore, high reproducibility between measurements, reliable quantitation, and low user errors due to automated operation are among the attributes that highlight the robustness of the technology [25,53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we showed that multiplexed immunoassays in nanocapillaries permitted simultaneous analysis of nine signaling pathways in cultured SH-SY5Y cells. Notably, nanofluidic protein PTM profiling is ideally suited for applications on clinical specimens due to its ultrasensitivity, where nanograms of tissue lysates are sufficient for the detection of picograms of proteins of interest [12,13,21,52]. Furthermore, high reproducibility between measurements, reliable quantitation, and low user errors due to automated operation are among the attributes that highlight the robustness of the technology [25,53].…”
Section: Discussionmentioning
confidence: 99%
“…Multiplexed nanofluidic protein posttranslational modification (PTM) profiling assays were used to measure the activities of nine signaling pathways in cultured SH-SY5Y neuronal cells following treatment with CBD oils. Previously, nanofluidic protein PTM profiling was used to identify aberrant signaling activities in tissue biopsies of nonalcoholic fatty liver disease and breast carcinoma [11][12][13]. Recently, nanofluidic protein PTM profiling was used to further differentiate copaiba essential oils with identical GC-MS chemical profiles [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, changes in FABPs were previously shown to occur in many common disorders. Dysregulation was established for FABP3 in cardiovascular disorders [ 56 , 61 ], FABP1, FABP2, FABP4 and FABP5 in non-alcoholic fatty liver disease [ 56 , 62 ] and FABP5 and FABP7 in cancer [ 56 , 63 , 64 ]. Although this excludes the dystrophinopathy-associated change in liver FABP5 as a robust and highly specific biomarker of X-linked muscular dystrophy, altered FABP5 levels may nevertheless be useful as a general pathophysiological marker in conjunction with other disease indicators.…”
Section: Discussionmentioning
confidence: 99%
“…11 Microvesicular steatosis may indicate mitochondrial dysfunction and deficiencies in fatty acid oxidation. 20,21 Recurrent hypoglycemia, global developmental delay, seizures, and cognitive FIG. 4.…”
Section: Role Of Adk For Hepatic Metabolismmentioning
confidence: 99%